Effective Strategy for Increase Awareness Culture Safety Among Workers: Analysis Literature - Wijayanto, Christiadi; Arifin, Antoni Ludfi (Dinasti International Journal of Management Science, 2025)
Understanding to culture safety is element key in create a comfortable work area as well as productive. This research aiming For analyze efficient strategies in upgrade understanding culture safety in the group workers sourced from literature? previous. This study using the procedure analysis literature against 23 journals that reviewed aspect culture safety, attitude workers, as well as implementation system management safety in various industrial zones. The results of the analysis display when approach based on training, efficient communication, involvement? management, as well as implementation "no policy no-blame culture" is a key strategy that contributes to improving understanding culture safety. Not only that, approach innovative kind of usage technology intelligence artificial intelligence (AI) was also found efficient in support management information safety as well as prediction risk, so that strengthen understanding worker to importance culture safety . This study formulate if holistic strategy implementation, linking worker in taking decision safety, and commitment prolonged from management is step means for upgrade understanding culture safety on site Work.